Refining tacrolimus dosing through CYP3A5 pharmacogenetics in Taiwanese renal transplant recipients - Yen-Lin Chang; Tzu-Hung Hsiao; Yi-Ming Chen; Ching-Heng Lin; Yi-Ju Liao; Chiann-Yi Hsu; Yung‑Po Liaw; Cheng-Hsu Chen (Renal Failure, 2025)
Genetic polymorphisms in CYP3A5 affects tacrolimus (Tac) bioavailability; however the optimal genotype-guided starting dose remains undefined. This retrospective cohort study examined the effects of the CYP3A5 allele on Tac pharmacokinetics in 431 Taiwanese renal transplant recipients. Genotyping was performed using the Axiom Genome-Wide TWB 2.0 array, with dose requirements and blood concentrations analyzed at multiple postoperative time points. CYP3A5 *3/*3 carriers required the largest dose reductions and exhibited the highest rate of Tac overexposure events (34.14%). Based on these results, we back-calculated an initial dosing formula to demonstrate that reducing doses for poor metabolizers (PMs) using a genotype-guided approach in our population could lower the risk of overexposure. Although preliminary, a genotype-guided initial dosing strategy reduced the likelihood of Tac overexposure by 69% (OR = 0.307, p = 0.018). These findings highlight the importance of identifying CYP3A5 poor metabolizers (*3/*3) for personalized therapy to minimize the risk of overexposure. Preemptive pharmacogenetic testing shows promise for enhancing dosing precision and treatment safety in Taiwanese patients.